Effect of Annealing Temperature on The Some Electrical Properties of InSb:Bi Thin Films (Baghdad Science Journal, 2025)
InSb alloy was prepared then InSb:Bi films have been prepared successfully by thermal evaporation technique on glass substrate at Ts=423K. The variation of activation energies(Ea1,Ea2)of d.c conductivity with annealing temperature (303, 373, 423, 473, 523 and 573)K were measured, it is found that its values increases with increasing annealing temperature. To show the type of the films, the Hall and thermoelectric power were measured. The activation energy of the thermoelectric power is much smaller than for d.c conductivity and increases with increasing annealing temperature .The mobility and carrier concentration has been measured also.